Scenario-based software architecture reengineering - Bengtsson, P.; Bosch, J. (Fifth International Conference on Software Reuse : proceedings : June 2-5, 1998, Victoria, British Columbia, Canada, 1998)
The paper presents a method for reengineering software architectures. The method explicitly addresses the quality attributes of the software architecture. Assessment of quality attributes is performed primarily using scenarios. Design transformations are done to improve quality attributes that do not satisfy the requirements. Assessment and design transformation can be performed for several iterations until all requirements are met. To illustrate the method we use the reengineering of a prototypical measurement system into a domain-specific software architecture as an example.